Home-made masks with filtration efficiency for nano-aerosols for community mitigation of COVID-19 pandemic - Li, I.W.-s. (Public Health, 2020)
OBJECTIVES: The novel coronavirus disease 2019 (COVID-19) epidemic that emerged in December 2019 has rapidly evolved in recent months to become a worldwide and ongoing pandemic. Shortage of medical masks remains an unresolved problem. This study aims to investigate the filtration efficiency (FE) of home-made masks that could be used as alternatives for community mitigation of COVID-19. STUDY DESIGN: Experimental observational analytic study. METHODS: The FE of home-made masks and medical masks (as the control) were tested under laminar flow within a scaled air duct system using nebulised NaCl aerosols sized 6–220 nm. The size-resolved NaCl aerosol count was measured using a scanning mobility particle-sizer spectrometer. Home-made masks with an external plastic face shield also underwent a splash test. In addition, the fibre structures of medical masks were studied under an electron microscope after treatment with either 75% alcohol or soap and water at 60 °C. RESULTS: The FE of the home-made masks at 6–200 nm were non-inferior to that of medical masks (84.54% vs 86.94%, P = 0.102). Both types of masks achieved an FE of 90% at 6–89 nm. A significantly higher FE was achieved when one piece of tissue paper was added adjacent to the inner surface of the medical mask than medical mask alone (6–200 nm: 91.64% vs 86.94%, P < 0.0001; 6–89 nm: 94.27% vs 90.54%, P < 0.0001; 90–200 nm: 82.69% vs 73.81%, P < 0.0001). The plastic face shield prevented the home-made mask from fluid splash. The fibre structures of the external surface of medical masks were damaged after treatment with either 75% alcohol or soap and water at 60 °C. CONCLUSIONS: The home-made masks in this study, which were made of one piece of tissue paper and two pieces of kitchen towels, layered from face to external, had an FE at 6–200 nm non-inferior to that of medical mask materials, which had a certified FE of ≥95% at 3 μm. In the current COVID-19 pandemic with the shortage of medical masks, these home-made masks combined with an external plastic shield could be used as an alternative to medical masks for community mitigation. In addition, one piece of tissue paper could be placed adjacent to the inner surface of a medical mask to prolong effective lifespan of the medical mask. These demand reduction strategies could be used to reserve medical masks for use in healthcare and certain high-risk community settings, such as symptomatic persons, caregivers and attendees to healthcare institutions.